Presence of Anti-Glomerular Basement Membrane Antibodies and Myeloperoxidase Anti-Neutrophilic Cytoplasmic Antibodies in a Case of Rapidly Progressive Glomerulonephritis - Mavani, Gaurang P.; Pommier, Max; Win, Sandar; Michelis, Michael F.; Rosenstock, Jordan (Frontiers in Medicine, 2015)
A 69 year old male developed rapid deterioration of kidney function and developed uremic symptoms. Creatinine was 486.2 µmol/L (5.5 mg/dl) on presentation. Anti-MPO was positive (titer>8 units, normal <0.4). He was clinically diagnosed with rapidly proliferative glomerulonephritis (RPGN) most likely due to ANCA vasculitis. He received three doses of pulse methylprednisone therapy. Kidney biopsy showed pauci-immune glomerulonephritis. Immunofluoroscence was also positive for faint linear staining of glomerular basement membrane. Anti GBM antibody was positive 2.1U (normal <1). He was started on high dose oral steroids, monthly intravenous cyclophosphamide and plasmapharesis was also initiated. His symptoms improved and creatinine is 247.5 µmol/L (2.8mg/dl). His repeat anti GBM antibody was negative. This is a rare case of rapidly progressive glomerulonephritis due to dual MPO-ANCA antibodies and anti GBM antibodies (DAV).